2015
DOI: 10.1111/eth.12407
|View full text |Cite
|
Sign up to set email alerts
|

Nest Defence Behaviour and Testosterone Levels in Female Pied Flycatchers

Abstract: Nesting holes are a scarce resource for obligated cavity-nesting birds and an important selective force for the evolution of aggressive female behaviours, which may be mediated by testosterone (T) levels. It is known that during periods of intense intrasexual competition such as initial breeding stages, females are highly aggressive towards intruding females. Here, we studied the implications of T levels for female-female competition by comparing levels of aggressiveness towards simulated female intruders (dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 84 publications
(105 reference statements)
3
22
0
Order By: Relevance
“…The link between plasma androgen levels and intra-sexual competition has been extensively studied under the “challenge hypothesis” [21], which states that, during reproduction, plasma T correlates positively with male-male competition. In females, although there are fewer studies than in males, similar hormonal responses to social challenges have been observed [16, 18, 22, 23], yet studies have also reported no link, or even negative correlations between female-female competition and circulating plasma androgen levels [19, 2427]. Given these contradictory findings, further research is required to clarify the relationship between intra-sexual competition and circulating androgens in females.…”
Section: Introductionmentioning
confidence: 99%
“…The link between plasma androgen levels and intra-sexual competition has been extensively studied under the “challenge hypothesis” [21], which states that, during reproduction, plasma T correlates positively with male-male competition. In females, although there are fewer studies than in males, similar hormonal responses to social challenges have been observed [16, 18, 22, 23], yet studies have also reported no link, or even negative correlations between female-female competition and circulating plasma androgen levels [19, 2427]. Given these contradictory findings, further research is required to clarify the relationship between intra-sexual competition and circulating androgens in females.…”
Section: Introductionmentioning
confidence: 99%
“…UV reflectance of white patches has been analyzed in other studies of the species (Lehtonen et al , Sirkiä and Laaksonen ). In this study we focus on the area of these plumage patches as in other studies of the species (Galván and Moreno , Lehtonen et al , Lobato et al , Moreno et al , , , Cantarero et al , , Laaksonen et al , Sirkiä et al , Plaza et al ). Moreover, we have previously shown that area and UV reflectance of wing patches are positively correlated, at least in females (Cantarero et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Effects of the social environment on female endocrine physiology and body mass (Bonenfant et al, 2009;DeVries et al, 2003;Eisenegger et al, 2011) provide proximate mechanisms through which reproduction and offspring can be affected. In birds, increasing group size, for example, is thought to exacerbate intraspecific competition, which can affect body mass (Asghar Saki et al, 2012;Keeling et al, 2003;Onbasilar and Aksoy, 2005) and circulating levels of steroid hormones such as corticosterone and androgens (Cantarero et al, 2015;Cunningham et al, 1987;Koelkebeck and Cain, 1984;Langmore et al, 2002;Mazuc et al, 2003;Onbasilar and Aksoy, 2005;Raouf et al, 2006;Smith et al, 2005). In Japanese quail, frequent changes in the group composition of breeding females are thought to reflect increased social densities and lead to elevated plasma corticosterone concentrations (Guibert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%